In situ XRD investigation of the evolution of surface layers on Pb-alloy anodes. (22nd August 2017) - Clancy, Marie; Styles, Mark J.; Bettles, Colleen J.; Birbilis, Nick; Kimpton, Justin A.; Webster, Nathan A. S.
Abstract : The electrochemical behaviour of a number of Pb-based anode alloys, under simulated electrowinning conditions, in a 1.6 M H2 SO4 electrolyte at 45 °C was studied. Namely, the evolution of PbO2 and PbSO4 surface layers was investigated by quantitative in situ synchrotron X-ray diffraction (S-XRD) and subsequent Rietveld-based quantitative phase analysis (QPA). In the context of seeking new anode alloys, this research shows that the industry standard Pb-0.08Ca-1.52Sn (wt%) anode, when exposed to a galvanostatic current and intermittent power interruptions, exhibited poor electrochemical performance relative to select custom Pb-based binary alloys; Pb–0.73Mg, Pb–5.05Ag, Pb–0.07Rh, and Pb–1.4Zn (wt%). The in situ S-XRD measurements and subsequent QPA indicated that this was linked to a lower proportion of β -PbO2, relative to PbSO4, on the Pb-0.08Ca-1.52Sn alloy at all stages of the electrochemical cycling. The best performing alloy, in terms of minimisation of overpotential during normal electrowinning operation and minimising the deleterious effects of repeated power interruptions – both of which are significant factors in energy consumption – was determined to be Pb–0.07Rh.